Transformative Education for Sustainable Development in Africa (2023)
The paper examined indigenous education in Africa and mental magnitude as one of the outcomes of educational process which can bring about desired transformation. The paper went further to explore the process of decolonising education in Africa. In conclusion, it is submitted that Africa's underdevelopment was to a great extent, a result of the imposed type of educational System by the west and Europe on Africa, which has proved to be a mis-fìt for most African countries. The paper recommended decolonisation of education in Africa while the indigenous System of education should be accorded recognition through globalisation